Female Labour Supply, Flexibility of Working Hours, and Job Mobility in the Netherlands - Rob Euwals (Institute for the Study of Labor (IZA), 1999)
In the empirical literature on labour supply, several static models are developed to incorporate constraints on working hours. These models do not address to what extent working hours are constrained within jobs, and to what extent working hours can be adjusted by means of changing employer. The aim of this paper is to measure the flexibility of working hours within and between jobs by utilizing subjective information on individual preferences to adjustments in working hours. The potential endogeneity of both the subjective information and job mobility will be taken into account. Furthermore, we argue that the Netherlands is an interesting country for the study of working hour flexibility, as part-time employment is fairly common. Empirical analysis based on a sample of employed women in the Dutch Socio- Economic Panel (1987-1989) shows, however, that the flexibility of working hours within jobs is low. Job mobility is a means of adjustment in working hours mainly for women who want to work more hours.
Keywords: C20; J60; J22; 330; Labour supply; hours restrictions; job mobility; Frauenerwerbstätigkeit; Arbeitsangebot; Arbeitszeitflexibilisierung; Arbeitsmobilität; Teilzeitarbeit; Schätzung; Niederlande